Green Mobility : Why Green Transport Interventions Matter for Sustainable Mobility - Dalkmann, Holger; Fischer, Alyssa; Peet, Karl (World Bank, Washington, DC, 2018)
As one of the four global goals framing sustainable mobility in the Global Mobility Report (GMR), green mobility aims to reduce both air and noise pollution from transport, and to address climate change in the transport sector through mitigation and adaptation. Transport currently contributes to 23 percent of global energy-related greenhouse gas (GHG) emissions and 18 percent of all man-made emissions in the global economy. In one projection, energy related carbon dioxide (CO2) emissions are expected to grow by 40 percent between 2013 and 2040.1 Air pollution—both ambient (outdoor) and household (indoor)—is the biggest single environmental risk to health; ambient air pollution alone kills about three million people each year. In addition, evidence from several countries suggests that traffic noise has the second biggest environmental impact on health.